Clinical and pathological heterogeneity of four common fusion subtypes in Xp11.2 translocation renal cell carcinoma - Guo, Wei; Zhu, Yiqi; Pu, Xiaohong; Guo, Hongqian; Gan, Weidong (Frontiers in Oncology, 2023)
Xp11.2 translocation renal cell carcinoma (Xp11.2 tRCC) is a highly heterogeneous renal cell carcinoma. The translocation involves TFE3 and different fusion partners. To explore the clinicopathological features of different fusion subtypes, we screened out 40 Xp11.2 tRCC. SFPQ-TFE3 and NONO-TFE3 fusion were classified in DBHS group, while ASPL-TFE3 and PRCC-TFE3 fusion were classified in non-DBHS group. Results showed that lymph node metastasis (P=0.027) and distant metastasis (P=0.009) were more common seen in non-DBHS family group than DBHS family group and cases in DBHS family group have better progressive-free survival (P=0.02). ASPL-TFE3 fusion was associated with worse outcome (P=0.03) while NONO-TFE3 fusion (P=0.04) predicted a better prognosis. The impact of fusion partners on clinical characteristics of Xp11.2 tRCCs deserves further exploration.